Studies on curing kinetics of polyphenylene sulfide: An insight into effects of curing temperature and time on structure and thermo‐mechanical behavior. Issue 12 (7th November 2021) - Chen, Guowei; Rodriguez‐Uribe, Arturo; Wu, Feng; Mohanty, Amar K.; Misra, Manjusri
Abstract: Polyphenylene sulfide (PPS) is a type of thermoplastic that has high thermal and mechanical performances and extensive applications. Before processing, pre‐curing is required to improve its processability and mechanical properties. Here, effects of curing temperature (245 and 260°C) and time (10, 30, 60, and 120 min) on structure and thermal‐mechanical behavior of PPS were studied through melt flow index (MFI), rheology, Fourier‐transform infrared spectroscopy, and thermal‐mechanical characterizations. The MFI was decreased from 700 g/10 min to less than 100 g/10 min (315°C/5.0 kg) after 60 min of curing at two different temperatures, greatly improving the processability of PPS in melt extrusion and injection molding processes. The functional groups remained unchanged after curing, due to the main reactions of chain extension and scission that occurred. For the PPS cured both at 245 and 260°C, the samples cured for 10 min displayed the highest degree of crystallinity and heat deflection temperature but had the lowest glass transition temperatures. The coefficient of linear expansion of PPS cured at 260°C showed anisotropy on flow and normal directions, which greatly differed from the PPS cured at 245°C. This study promotes an improved understanding of the curing process for solid PPS. Abstract : The curing was performed within a temperature‐controlled oven that is connected to the outside air through its vent. The MFI was decreased from 700 g/10 min to less than 100 g/10 min (315°C/5.0 kg) after 60 min curing at two different temperatures, greatly improving the processability of PPS in melt extrusion and injection molding. The functional groups are not changed after curing, which is due to that the chain extension and scission are the main reactions occurred.